دلالة تشبيه الصدقة في القرآن الكريم والاستفادة منه في تربية النفس على الصدقة - Daris Musthofa; Muhammad Ahnaf Aqil (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2023)
Allah made the Arabic language a large part of the service of the Holy Quran, and the miracles of the Quran are a (balaghi) and (bayani). This research focuses on one of the sections for the bayan, which is the tashbih in the Holy Quran linked to charity, and there are three verses, 261, 265 and 264 of surah Al-baqara. All these verses use the (uslub tashbih) of a similar type the (tashbih mursal), considering the mention of its (adah tashbih), and they are by the representative analogy (tashbih at-tamtsili), in consideration of the wajhu shibhi. They are also included in the (tashbih mujmal); therefore, the wajhu shibhi is not mentioned directly. This method greatly affects the souls because it depicts the greatness of the reward of charity and its impact in this life and the Hereafter in the best way, and it transfers souls from a moral world to a material world. This raises a person's interest in charity and drives him to fulfill it because he has found in his mind an image of what he will get out of his charity.